TINJAUAN YURIDIS TINDAK PIDANA PENYALAHGUNA NARKOTIKA GOLONGAN I BUKAN TANAMAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA (STUDI PUTUSAN NOMOR 621/PID.SUS/2020/PN.JKT.BRT): Indonesia - Wijaya, Syafrudin; R. Gultom, Elfrida (Universitas Ekasakti, 2023)
Drug abusers should get rehabilitation punishment because rehabilitation is an alternative form therefore abusers are guaranteed by the narcotics law to get rehabilitation sentences instead of imprisonment, Such as the case of Buchari Hy Bin Hamdan Yahya, legally proven and convinced guilty of committing the crime of